HISTORY OF THE SOCIO – POLITICAL DEVELOPMENT OF THE CHOCH OASIS IN THE 6TH-8TH CENTURIES (International journal of artificial intelligence, 2025)
This article explores the socio – political development processes of the Choch oasis in the 6th-8th centuries. As a result of the choch Oasis being part of the Turkish Khaganate, political and economic life developed rapidly in the area. Trade and craft centers expanded in the cities and irrigation systems were improved. Cultural ties between Sughd traders and the local population were strengthened. However, as a result of the Arab Caliphate's raiding campaigns in the first half of the 8th century, the Oasis faces an economic crisis and most of the cities are destroyed. The study analyzes the political life, cities, defense system and influence of arab invasions of the choch Oasis based on historical and archaeological sources.